(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Passive Ultra-High-Frequency Radio Frequency Identification (UHF RFID) tag has been implemented as a wearable device for numerous healthcare applications. However, the tag possesses limitations owing to the absorption of electromagnetic radiation by the human body, which significantly reduces the read range of the tag. Thus, the potential strategies to mitigate the effect of the human body need to be addressed. Recently, significant efforts have been made to overcome this shortcoming by incorporating metamaterials or introducing slots to the tag antenna structure. Therefore, this article provides insight into strategies that specifically employ slots, Artificial Magnetic Conductor (AMC), and Split Ring Resonator (SRR). Prior to this, the factors affecting the read range and previously reported studies are briefly discussed. Finally, the future directions for further improvement of these strategies are discussed.